Estimating the Shelf Life of Balado “DR” Cassava Chips Based on Free Fatty Acid Parameters with the Accelerated Shelf-Life Test Method Arrhenius Model - Sari, Yuliana; Juwitaningtyas, Titisari (Journal of Applied Food Technology, 2022)
Balado cassava chips are one of the processed cassava chips wrapped with Balado seasoning. Balado cassava chips “DR” is one of the cassava chips produced in Sleman, Yogyakarta. The Balado “DR” cassava chip product that has been marketed to shops does not include an expiration date. Whereas information about the shelf life of a food product is one of the important details to be included on the label or packaging. It aims to ensure the quality and safety of a food product when it reaches consumers. During storage, Balado cassava chips can experience a decrease in quality in the form of rancidity caused by the fat content in Balado seasoning due to the hydrolysis process. Free fatty acid analysis or FFA can be used to measure quality degradation caused by the hydrolysis process. The purpose of this study was to estimate the shelf life of Balado “DR” cassava chips based on FFA parameters. The method of estimating the shelf life used is the Accelerated Shelf-Life Test (ASLT) Arrhenius Model. The test parameter used is Free Fatty Acid (FFA). Observations were made every 5 days at 40°C for 20 days and every 7 days at 30°C and 50°C for 28 days. The results showed that the higher the temperature and storage time, the higher the FFA contents. So that the quality of cassava chips decreases with increasing FFA value. Based on FFA analysis, the estimated shelf life of Balado “DR” cassava chips at storage temperatures of 30℃, 40℃ and 50℃, respectively, is 20 days, 18 days and 16 days.